The Effect of Acceptance-Based Behavior Therapy on Body Mass Index among Patients with Premature Coronary Heart Disease - Eshagh Samkhaniani; Farhad Jomehri; Hasan Ahadi; Javad Khalatbari (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Obesity is a known risk factor for cardiovascular diseases; however, weight loss and decreasing body mass index (BMI) are difficult for many patients with coronary heart disease. The purpose of this study was to determine the effectiveness of acceptance-based behavior therapy on BMI among patients with premature coronary heart disease. Materials and Methods: This study was conducted in the summer of 2018 and was of quasi-experimental design with control group, pre-test, post-test, and a follow-up period after 3 months. The statistical population included all male patients with premature coronary heart disease who were younger than 50 years old and were referred to Shahid Rajaee hospital in Tonekabon, among whom 24 were selected via convenience sampling method and divided into two intervention and control groups. The intervention group received treatment-based behavioral therapy for eight weekly sessions while the control group did not receive any intervention. BMI was calculated in the pre-test, post-test and follow-up for each participant. Data were analyzed via SPSS software version 22. Results: In the experimental group, the mean (SD) BMI decreased from 32.2 (3.4) before the intervention to 31.5 (3.1) after the intervention (P<0.01). In the control group, the mean (SD) BMI decreased from 32.6 (3.5) before the intervention to 32.5 (3.4) after the intervention; however, the decrease was not statistically significant. In addition, in the follow-up phase of the experimental group, the mean (SD) BMI decreased from 31.5 (3.1) in post-test to 30.4 (2.8) in the follow-up (P<0.001). In the control group, the mean (SD) BMI decreased from 32.5 (3.4) in post-test to 32.4 (3.4) in the follow-up; however, this decrease was not statistically significant. Conclusion: It could be concluded that acceptance-based behavioral therapy lead to a decrease in BMI among premature coronary heart disease patients.